Aslanger Pattern: An unusual electrocardiogram in Acute pulmonary Embolism - Abdi IA; Abdi AE; Hassan MO; Ahmed SA; Waberi MM; Aden AS; Dahir OF; Mohamud MA; Ali II; Jama SMA; Dirie AMH; Arın CB (Research Reports in Clinical Cardiology, 2024)
Ishak Ahmed Abdi,1 Ahmed Elmi Abdi,1 Mohamed Omar Hassan,1 Said Abdirahman Ahmed,1 Mohamud Mire Waberi,1 Ahmed Shafie Aden,1 Osman Farah Dahir,1 Mohamed Ahmed Mohamud,2 Irshad Ibrahim Ali,3 Shuayb Moallim Ali Jama,4 Abdirahman Mohamed Hassan Dirie,5 Can Baba Arın6 1Department of Cardiology, Mogadishu Somali Türkiye Training and Research Hospital, Mogadishu, Somalia; 2Internal Medicine Resident, Kenyatta National Hospital, Nairobi, Kenya; 3Anesthesia and Critical Care Unit, Mogadishu Somali Türkiye Training and Research Hospital, Mogadishu, Somalia; 4Department of Radiology, Mogadishu Somali Türkiye Training and Research Hospital, Mogadishu, Somalia; 5Respiratory Medicine Department, Mogadishu Somali Türkiye Training and Research Hospital, Mogadishu, Somalia; 6Department of Cardiology, Health Science University, Dr. Siyami Ersek Thoracic and Cardiovascular Surgery Center, Training and Research Hospital, İstanbul, TurkeyCorrespondence: Ishak Ahmed Abdi, Department of Cardiology, Mogadishu Somali Türkiye Training and Research Hospital, Second Street, Black Sea, Hodan District, Mogadishu, Somalia, Tel +252618439596, Email isakabdi70@gmail.comIntroduction: Pulmonary embolism (PE) is a critical condition that can present with diverse and often non-specific electrocardiographic findings. The Aslanger pattern, identified in 2020, is an uncommon electrocardiography (ECG) finding typically associated with acute non-ST-segment elevation myocardial infarction (NSTEMI). Although this pattern is usually linked to myocardial infarction with significant coronary stenosis, we report a rare case where the Aslanger pattern was observed in a patient with acute pulmonary embolism.Case Presentation: A 52-year-old male with Parkinson’s disease presented with sudden chest pain, shortness of breath, sweating, and fatigue. Initial ECG showed Aslanger pattern, suggesting acute coronary syndrome. Despite elevated troponin I (1624 ng/mL) and normal coronary angiography, further investigation revealed right ventricular dilation and massive pulmonary embolism confirmed by CT angiography. The patient was treated with thrombolytics and anticoagulation, stabilizing over five days and discharged on rivaroxaban.Conclusion: The Aslanger pattern usually linked to myocardial infarction can also occur in acute pulmonary embolism. This case underscores the need for careful differential diagnosis and timely treatment to prevent complications associated with delayed care.Keywords: pulmonary embolism, Aslanger pattern, electrocardiogram